The Per Jacobsson Foundation at 40 : Commemorating a Statesman in International Monetary Affairs. (per Jacobson lecture, 2004)
This paper discusses the appointment of Andrew Crockett as the Chairman of the Per Jacobsson Foundation. At its meeting on October 3, 2004, the Board of Directors of the Per Jacobsson Foundation unanimously selected Mr. Andrew Crockett as its new Chairman with effect from November 1. Mr. Crockett, a Director of the Foundation since October 1993, succeeds Mr. Jacques de Larosiere, Chairman since November 1999. Mr. de Larosiere announced his retirement from the Chairmanship and the Board of Directors in recognition of the age limit for directors of the Foundation agreed by the Board.